Minerals elements of human nutrition - Ryan, Kathleen O.; Poglitsch, Mike; Learning seed (Illinois : Learning Seed, 2009)
Described the differences between vitamins and minerals, and what defines a mineral as a major or trace
Vitamins & minerals -- Major minerals -- Trace
Title from title screen
Director of photography, Terry Brooks ; production assistant, Scott Loberger
Narrator: Bohus Blahut
DVD format
Keywords: Minerals in human nutrition; Trace elements in nutrition; Vitamins in human nutrition